The Effect Of Java Langgam Music Therapy As Adjuvant Therapy Towards Changes Blood Pressure In Hypertension Patients In Puskesmas Depok Ii Sleman Yogyakarta - Eva Marti; Arimbi Karunia Estri; Margareta Hesti Rahayu (Alma Ata University Press, 2019)
The prevalence of hypertension in Sleman Regency in 2015 was 33.2%, where hypertension was ranked second from the top ten outpatient diseases in the Puskesmas in Sleman Regency. Hypertension requires regular and continuous treatment to prevent further complications. Therefore, it is necessary to have complementary therapies as adjuvants such as Javanese music therapy as a therapeutic choice. Langgam Javanese music is classical music that has been well known by the people in Yogyakarta. The purpose of this study was to determine the effect of Javanese style music therapy on changes in blood pressure in hypertension patients in the control group and intervention group. This study was a quasi-experimental study that compared changes in blood pressure in the intervention group and the control group. The sample used was hypertensive patients who routinely treated in Depok II Health Center, as many as 60 people, 30 people in the intervention group and 30 people in the control group. The results showed that there difference in systolic and dyastolic blood pressure significantly in the intervention group compared to the control group with a value of P = 0,000 (<0.05). Langgam Jawa music therapy can be chosen as an adjuvant therapy for hypertensive patients in DI Yogyakarta.